Mencegah Kecanduan Gadget Pada Anak Upaya Meningkatkan Minat Baca Anak Melalui Peran Orang Tua Dan Rumah Baca Kita Di Dusun Kidul Desa Buniseuri - Pramudita, Aldi; Silvi Assania Turrohmah; Nurul Azmi Herdianti; Rifda Nur Azkiyah; Neng Nenis; Angga Shidiq; Nastiti Novitasari (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
This study aims to describe the role of parents in preventing gadget addiction in children in order to minimize obstacles in the process of child development. The research was conducted at Rumah Baca Kita Buniseuri, DusunKidul, Buniseuri, Cipaku, Ciamis, for two months from September 1 to November 1, 2024. A descriptive qualitative approach was used in this study with purposive sampling technique, which involved parents who actively use gadgets and play a role in children's learning at home. Data were collected through observation, interviews, data reduction, and documentation, and analyzed using the Miles and Huberman technique with triangulation for data validity. The results show that gadget addiction in children can be overcome by the active role of parents in supervising and limiting the use of gadgets, as well as encouraging children's interest in reading through reading together and utilizing public facilities such as Rumah Baca Kita. This research has important implications in efforts to improve the quality of child development through collaboration between parents and non-formal education facilities.